PENGARUHl PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS DAN MOTIVASI BELAJAR SISWA - Putri, Maharani Larasati; Isrok'atun, I.; Kurnia, Dadang (Jurnal Pena Ilmiah, 2017)
The underlying problem of this research is the lack of ability of elementary school students in interpreting mathematical problems concerning addition and subtraction of integers into certain images or symbols. Realistic Mathematics Education approach presents the stage to improve the ability of mathematical representation. The method used is quasi-experiment with non-equivalent control group. The samples grade IV of SDN Gudangkopi 1 as experimental class and SDN Palasari as control class. The instruments used in this research are question mathematical representation ability test, learning motivation attitude scale, teacher performance observation and student activity sheet, teacher and student interview sheet. The finding reveals that Realistic Mathematics Education approach shows improvement on the ability of mathematical representation with average value showing moderate gain, is then considered a better learning compared to the conventional one, and shows a positive relationship between students' mathematical representation ability and learning motivation.